P409 FMT induced increase in gut microbial diversity and Clostridia is associated with clinical response in patients with ulcerative colitis – results from STOP Colitis trial. (21st January 2022) - Quraishi, M N; Quince, C; Hewitt, C; Beggs, A; Gerasimidis, K; Sharma, N; Hawkey, P; Oo, Y; Ives, N; Manzoor, S; Loman, N; Hansen, R; et al.
Abstract: Background: Findings from five randomised trials using faecal microbiota transplantation (FMT) in adults with ulcerative colitis (UC) demonstrate therapeutic potential. The optimum methodology for administration of FMT is unclear. We describe a prospective, three centre, open-label randomised trial (STOP-Colitis pilot) that compared tolerability and efficacy of nasogastric (NG) versus colonic (COLON) routes of administration and identified potentially important host microbial interactions. Methods: Adult participants with active UC (partial Mayo score of ≥4 and ≤8) were randomised for administration of, 8 infusions of FMT over an, 8 week period either via the naso-gastric (NG) or colonic (COLON) route. Each patient was matched to a single FMT donor. Clinical response was defined as ≥3 point and ≥30% reduction in full Mayo score at week, 8 compared to baseline. Changes in faecal gut microbial diversity (Shannon's diversity) and composition before/after FMT were analysed with, 16S rRNA sequencing. Correlation between datasets was evaluated with Kendall's Tau coefficient. Results: Sixteen patients were randomised to NG;, 14 to COLON FMT. Seven participants in the NG and, 2 in the COLON arm withdrew before completion. Clinical response was achieved in, 9/12 [75%] for COLON vs, 2/8 [25%] for NG)., 12/14 (86%) COLON participants were protocol-adherent compared with, 8/16 (50%) for NG. For the COLON patients (N=8) an increase in alpha diversity was observed (P=0.01). For those patients that responded to FMT overall (N=9) there was a significant increase in alpha diversity (P<0.005) and lower faecal calprotectin levels in responders vs. non-responders (week, 4 to week, 8 mean, 508.6 ug/g vs, 853.6 ug/g respectively; P=0.03). Overall, there was a negative association between calprotectin levels and alpha diversity (tau =-0.29; P <, 0.005). Operational taxonomic units belonging to Clostridia deriving from the Christensenellaceae and Lachnospiracae families correlated with both reduced calprotectin and had high engraftment frequency (both false discovery rate corrected P<0.10). In a cohort of patients with mucosal immune cell analysis Clostridia positively correlated with gut homing Treg populations and negatively correlated with Th17 cells populations (P<0.005), suggesting that this group may play an important role in the immune response to FMT in UC. Conclusion: This pilot study suggests that in participants with active UC, FMT delivered via the colonic route appears to be better tolerated than via NG with a greater efficacy signal. There are signals linking gut microbial diversity and taxa belonging to Clostridia (short chain fatty acid producers) with clinical response, calprotectin and a shift towards an immunoregulatory phenotype.